2015
DOI: 10.1016/j.jhin.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus survival in aerosols and estimates of viable virus loss resulting from aerosolization and air-sampling

Abstract: Using a Collison nebulizer, aerosols of influenza (A/Udorn/307/72 H3N2) were generated within a controlled experimental chamber, from known starting virus concentrations. Air samples collected after variable suspension times were tested quantitatively using both plaque and polymerase chain reaction assays, to compare the proportion of viable virus against the amount of detectable viral RNA. These experiments showed that whereas influenza RNA copies were well preserved, the number of viable viruses decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 10 publications
2
29
0
2
Order By: Relevance
“…This is in agreement with previously documented works [40][41][42][43]. The success in collection of the virus in the second experiment was obtained at an air suspension time of 1.0 min, while shorter suspension times of 15.0, 30.0, and 45.0 sec failed in recovering the virus from the transport medium.…”
Section: Optimization Of the Impinger Variablessupporting
confidence: 91%
“…This is in agreement with previously documented works [40][41][42][43]. The success in collection of the virus in the second experiment was obtained at an air suspension time of 1.0 min, while shorter suspension times of 15.0, 30.0, and 45.0 sec failed in recovering the virus from the transport medium.…”
Section: Optimization Of the Impinger Variablessupporting
confidence: 91%
“…However, PCR-based methods typically cannot differentiate between viable and nonviable microbes. 32 A recent study found that PCR substantially overestimated the quantity of infectious airborne influenza virus, but the differences in infectious versus noninfectious virus over time were similar to data from quantification by plaqueforming units, which determined that virus losses were evident within 30-60 minutes postaerosolization. 32 Generally, enveloped viruses survive better at lower RH, but there are many exceptions.…”
Section: Environmental Factors That Influence Airborne Microbial Survmentioning
confidence: 74%
“…32 A recent study found that PCR substantially overestimated the quantity of infectious airborne influenza virus, but the differences in infectious versus noninfectious virus over time were similar to data from quantification by plaqueforming units, which determined that virus losses were evident within 30-60 minutes postaerosolization. 32 Generally, enveloped viruses survive better at lower RH, but there are many exceptions. 28 Other factors that affect aerosol activation in relation to RH include evaporative activity (ie, dehydration, rehydration), surface areas of particles, and pH.…”
Section: Environmental Factors That Influence Airborne Microbial Survmentioning
confidence: 74%
“…It must be noted that the PCR-based detection employed in this work determines a quantitative value of virus particles based on genetic material, and since it does not probe the complete and intact virus particles, it is not a complete analysis of influenza virus in terms of infective particles [9]. In fact, standard infectivity assays typically quantify virus by determining the amount required to produce cytopathic effects in 50% of cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Impingers are liquid collection-based samplers relying on working volumes of 5 or 20 mL, whereas filters and impactors are dry collection-based samplers relying on an elution step to extract the collected virus from their respective solid supports. This elution can result in a large final extracted sample volume, typically on the order of several milliliters [6, 911]. These large volumes engender enormous dilution if only a few viral particles are present in the sampled volume of air, making these methods unsuitable for low LoD measurements.…”
Section: Introductionmentioning
confidence: 99%